Destabilization of Regional Labour Markets in Ukraineunder Heightened Security Threats - Taras G. Vasyltsiv; Olha O. Levytska; Olha P. Mulska; Ruslan L. Lupak; Iryna R. Bodnar (Studia Regionalne i Lokalne)
This article focuses on the problems of the Ukrainian economy and its regional labour markets in the context of full-scale war. The main challenges to regional development in the short and long term are identified, and the critical trends in the social stability and labour supply and demand in the regions of Ukraine in the prewar period and during the war are characterized. The authors analyse the level of balance in regional labour markets and identify the main risks and threats to their functioning and development in the context of destabilization processes. The article outlines the prospects and priorities of the state policy of stabilizing the functioning and ensuring the development of regional labour markets in Ukraine.